Children with Cleft Palate: Predictors of Otologic Issues in the First 10 Years. (May 2019) - Funamura, Jamie L.; Lee, Janet W.; McKinney, Samantha; Bayoumi, Ahmed G.; Senders, Craig W.; Tollefson, Travis T.
Objective: To evaluate the characteristics of children with cleft palate associated with persistent otologic issues in the first 10 years of life. Study Design: Case series with chart review. Setting: Single academic center. Subjects and Methods: Children born with cleft palate from 2003 to 2007 and treated by the UC Davis Cleft and Craniofacial Team between January 2003 and December 2017 were included in the study. Data from 143 patients were analyzed via Wilcoxon rank sum and Fisher exact tests for univariate analysis and logistic regression to determine adjusted odds ratios. Results: The median length of follow-up was 9.9 years, and the age at last ear examination was 10.7 years. At the last evaluation, unresolved otologic issues were common, with at least 1 ear having a tympanic membrane (TM) perforation (16.1%), a tympanostomy tube (36.2%), or conductive hearing loss (23.1%). After adjusting for demographic and clinical characteristics, history of palate revision or speech surgery was associated with having a TM perforation ( P = .02). The only clinical variables associated with conductive hearing loss was the presence of a TM perforation ( P < .01) or a genetic abnormality ( P = .02). Severity of palatal clefting was not associated with specific otologic or audiologic outcomes after adjusting for other characteristics. Conclusion: A large proportion of children with cleft palate have persistent otologic issues at age 10 years and would benefit from continued close monitoring well after the age when most children have normalized eustachian tube function. Prolonged otologic issues were not found to be associated with cleft type.